Advances in Aerospace Guidance, Navigation and Control Selected Papers of the Fourth CEAS Specialist Conference on Guidance, Navigation and Control Held in Warsaw, Poland, April 2017 (Springer International Publishing, 2018)
The first three CEAS (Counsil of European Aerospace Societies) Specialist Conferences on Guidance, Navigation and Control (CEAS EuroGNC) were held in Munich, Germany in 2011, in Delft, Netherlands in 2013 and in Toulouse, France in 2017. The Warsaw University of Technology (WUT) and the Rzeszow University of Technology (RzUT) accepted the challenge of jointly organizing the 4th edition. The conference aims to promote scientific and technical excellence in the fields of Guidance, Navigation and Control (GNC) in aerospace and other fields of technology. The Conference joins together the industry with the academia research. This book covers four main topics: Guidance and Control, Control Theory Application, Navigation, UAV Control and Dynamic. The papers included focus on the most advanced and actual topics in guidance, navigation and control research areas: · Control theory, analysis, and design · ; Novel navigation, estimation, and tracking methods · Aircraft, spacecraft, missile and UAV guidance, navigation, and control · Flight testing and experimental results · Intelligent control in aerospace applications · Aerospace robotics and unmanned/autonomous systems · Sensor systems for guidance, navigation and control · Guidance, navigation, and control concepts in air traffic control systems For the 4th CEAS Specialist Conference on Guidance, Navigation and Control the International Technical Committee established a formal review process. Each paper was reviewed in compliance with good journal practices by independent and anonymous reviewers. At the end of the review process papers were selected for publication in this book.